Stimuli-induced modulation of white light emission in colloidal polymer particles: Design of chemosensors and dynamic chromism toward unclonable patterning and its classification based on machine learning - Mardani, Hanieh; Herizchi, Ata; Roghani-Mamaqani, Hossein (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Synthesis of light-, pH-, and thermo-responsive colloidal polymer particles,•Stimuli-induced modulation of white light emission using FRET phenomena,•Preparation of white light-emitting colloids, films, coatings, and diodes,•Design of pH chemosensors, dynamic anticounterfeiting inks, and unclonable patterns,•Authentication of the unclonable patterns using machine learning. Stimuli-responsive light-emitting materials have gained significant attention due to their potential applications in optoelectronic devices, chemosensors, anticounterfeiting inks, and unclonable encryption. Coumarin-containing fluorescent polymer particles with light-, pH-, and thermo-responsiveness were prepared by distillation-precipitation polymerization of hydroxyethyl methacrylate and 2-(dimethylamino)ethyl methacrylate. White light emission was observed by physical incorporation of hydroxyl-functionalized spiropyran (SPOH) into the colloidal polymer particles in a certain ratio of the colloidal polymer particles and SPOH content. The white light emission was obtained by modulating pH and temperature to finely tune the Förster resonance energy transfer process and cover the entire visible spectra from the emissive lights. This phenomenon was successfully used to prepare pH sensors, dynamic anticounterfeiting inks, unclonable patterning, and also white light-emitting colloids, films, coatings, and diodes. As an example, a white light-emitting diode was fabricated using the SPOH-doped colloidal polymer particles in poly(vinyl alcohol) matrix having Commission Internationale del'Eclairage color coordinates of (0.31, 0.33). Dynamic chromism and preparation of randomly distributed blue, red, and white light-emitting patterns are examples of advanced anticounterfeiting and encryption methods that were generated via the prepared low-cost environmentally friendly waterborne ink. For the authentication purpose of the unclonable patterns, the classification algorithms were designed based on machine learning to classify the true patterns from the false ones.